ANTI-DEFORESTATION MODELS ON SOCIAL FORESTRY SYSTEMS IN INDONESIA - Wartiningsih,; Nuswardani, Nunuk (International Journal of Psychosocial Rehabilitation, 2020)
The social forestry programs introduced by the government are controversial. Some argue that there is a paradigm shift on forest resource management leading consequently to economic equality for instance. However, many experts are worried about the deforestation that may be caused. The current research aims to find out the anti-deforestation models on social forestry systems by involving the roles of the regional government. In real, the groups of farmers are unknowledgeable to what they have to do, and they feel that the central government “ignored” them after receiving the social forestry certificate. This research employed two sources of data: primary and secondary. Primary data are associated with depth interview with the groups of famers receiving the certificates and secondary one includes the regulations that are relevant to the problems studied. The chosen data were prescriptively and qualitatively analyzed by applying the theories of forest resource management proposed by Ostrom.